8(x-6)=9+7x

Simple and best practice solution for 8(x-6)=9+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-6)=9+7x equation:


Simplifying
8(x + -6) = 9 + 7x

Reorder the terms:
8(-6 + x) = 9 + 7x
(-6 * 8 + x * 8) = 9 + 7x
(-48 + 8x) = 9 + 7x

Solving
-48 + 8x = 9 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-48 + 8x + -7x = 9 + 7x + -7x

Combine like terms: 8x + -7x = 1x
-48 + 1x = 9 + 7x + -7x

Combine like terms: 7x + -7x = 0
-48 + 1x = 9 + 0
-48 + 1x = 9

Add '48' to each side of the equation.
-48 + 48 + 1x = 9 + 48

Combine like terms: -48 + 48 = 0
0 + 1x = 9 + 48
1x = 9 + 48

Combine like terms: 9 + 48 = 57
1x = 57

Divide each side by '1'.
x = 57

Simplifying
x = 57

See similar equations:

| 22+20x=4x | | 5(0)-7x=-7(5+x) | | 7z+7-5z=9+z-3 | | 138.80=0.09x+3.80 | | 7x-13+9=2+x | | -8(-2m+10)=-9+8(10m-10) | | 7k^2+2=-37 | | (x/1)+(1/x)=61/30 | | x^2-4-3x=0 | | sqrt(2x+3)=5 | | 6(x-.08)-0.2(5x-4)=6 | | 4/5x-7=-1/5x-7 | | w^2-26w-42=0 | | x/1+1/x=61/30 | | x-2+2x/7=-2+9x/7 | | 2.39x+100=5.7121+10x | | x^2-4+3x=0 | | -7(x-8)=-6x-6 | | 2.39+100=5.7121+10 | | 4y+3=6y-3y | | -5x+3=2x+31 | | 2x-4(x+1)=-2x+20 | | z-7/9z-63 | | 3x^2+8x-21=0 | | -17/4y | | 1/2*3/1 | | -6(1+2x)=-2(11+2x) | | 2[x-(4x-9)]=3x+4 | | 2[x-(4x-9)]=3b+4 | | 3/2x-11+x=4x-3 | | 5x+4x=8x-7 | | -2(12-2p)=-8(p+6)+4p |

Equations solver categories